Analiza politične usmeritve in označevanja političnih strank v Evropskem parlamentu - Nahtigal, Miha (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2018)
This article explores the political parties in the 8th European Parliament on the basis of roll-call vote analysis. Besides the left-right divisions, we have also analysed the nationalist-globalist political cleavage. We have compared the resulting party positions with their left-right wing party labels. In addition, we have focused on inconsistencies and biased existing labels and the geopolitical interests connected with the current way of labelling. We have found out that the current way of left-right labelling privileges a globalist and liberal position, while some other political positions were not even represented. Finally, we have presented a new way of political labelling, which would also include a nationalist-globalist cleavage.
Keywords: Evropska unija; parlamenti; politična geografija; politične stranke